Potential exploitation of avian resources by fossil hominins: An overview from ethnographic and historical data. (9th November 2016) - Negro, Juan José; Blasco, Ruth; Rosell, Jordi; Finlayson, Clive
Abstract: Human consumption of bird meat in modern societies comes in two ways: as embryos –i.e., eggs- and as hatched individuals, either young or adults. Poultry provide nowadays about one-third of the animal proteins and fat in human diets, but the bird–human interface is possibly an ancient one. Hundreds of species are kept as pets and non-edible products, such as feathers or eggshells are used by traditional cultures in all continents as body ornaments, headdresses or jewelry. Regarding fossil hominins, it has been reported that Neanderthals decorated themselves with raptors and corvid feathers. It is also known that they consumed birds, including pigeons, according to cut marks in bone remains. Even if birds may be perceived as elusive prey due to their flight capabilities, they are forced to incubate their eggs in a fixed position, the nest, where the nestlings grow until they reach full size. This makes eggs, nestlings and brooding adults easy prey. Roosting birds are practically defenseless against stealth predators. And humans may become such when they learn to interpret cues left behind by the birds themselves. Birds share a common sensitive world with humans. Most birds are diurnal as we are, and they rely on visual and auditive cues for communication, that we may learn to interpret, or that we can even imitate.